A szentírástudomány (biblikum) oktatása az Országos Rabbiképző Intézet első 50 évében - Oláh, János (Gerundium, 2011)
Teaching Scriptural Scholarship (Biblical Studies) in the First 50 Years of the National Institute of Rabb inical Training. Focusing on the first 50 years of its existence, this survey first offers a brief outline of the early history of the Institute of Rabbinical Training (established in Budapest in1877), then it takes stock of the most distinguished representatives of teaching scriptural scholarship (biblical studies) there, the subjects they taught, as well as the completed doctoral dissertations relevant to the field. The review also includes a detailed bibliography of the Institute’s history.